Critical Study of Business Competition Supervisory Commission’s Authority in Handling Business Competition Violations - Latif, Inas Sofia; Pangestu, Ilham Aji; Fadhlillah, Muhammad Rizqi (Fakultas Hukum Universitas Muhammadiyah Sorong, 2023)
The purpose of this study is to criticize the authority of the Business Competition Supervisory Commission (KPPU) in overcoming and resolving business competition violations. The authority in question is regulated in Law Number 5 of 1999 concerning the Prohibition of Monopoly Practices and Unfair Business Competition (Business Competition Law) jo. Law Number 11 of 2020 concerning Job Creation. According to the provisions of laws and regulations, KPPU acts as an independent state auxilary organ. At the practical level, KPPU exercises the authority to investigate, prosecute, and decide. Normative legal research is used by researchers to answer related problems through a legal approach and a comparative approach with literature study methods. The results showed that the implementation of KPPU's authority in handling business competition violations can be said to be still not optimal. Researchers suggest that the ideal authority policy in handling business competition violations can refer to several countries that have similar business competition law enforcement agencies by making adjustments to business competition conditions in Indonesia.